Manajemen Strategik Pemasaran Lembaga Pendidikan Islam dalam Menarik Minat Calon Peserta Didik di Era Digital - Eka Diana; Hizamul Fikri Aditama (Jurnal Manajemen dalam Pendidikan, 2025)
This research aims to identify and analyze marketing management strategies implemented by Islamic educational institutions in the digital era to attract prospective students, as well as to examine the challenges and opportunities that arise. Employing a qualitative approach with a descriptive-analytical literature study, this research examines various relevant sources such as scientific journals, books, and proceedings. The findings indicate that the management of Islamic educational institutions actively utilizes digital marketing strategies, including the use of social media, engaging visual content, leveraging testimonials, and implementing the 7P marketing mix. These strategies have proven effective in increasing institutional visibility, expanding information reach, and directly contributing to an increase in student enrollment. However, their implementation faces significant challenges related to digital ethics, content quality and authenticity, potential distractions, and digital competency and infrastructure gaps. This study highlights the emergence of "Islamic value marketing" as a holistic approach that integrates digital strategies with Islamic ethical principles, creating a unique appeal and building trust beyond mere commercial aspects. The implications of this research emphasize the need for continuous digital literacy training and the development of clear digital ethical guidelines, as well as the development of a more comprehensive Islamic education marketing management model that considers adaptive leadership and multi-stakeholder collaboration.